Implementation of Forward Chaining for Diagnosis of Dengue Hemorrhagic Fever - Isa Bahroni; Linda Perdana Wanti; Nur Wahyu Rahadi; Antonius Agung Hartono; Riyadi Purwanto (Journal of Innovation Information Technology and Application (JINITA), 2022)
Insects in the form of mosquitoes are transmitting vectors of several types of diseases that are quite dangerous and need to be watched out for because they can be deadly, such as dengue fever mosquitoes, malaria, elephantiasis and the like. Patients suffering from mosquito-borne diseases must be treated immediately to find out the type of disease they are suffering from and their treatment solutions. The era of digitalization that is growing rapidly, including in the field of medical science, makes the use of information technology to help improve quality services for the community. The analysis used in this research is using the forward chaining method, as a comparison of the overall process of the problems obtained in the investigation and developed using the waterfall paradigm. Forward chaining is implemented because the disease diagnosis process begins by observing the symptoms experienced by a patient and then continues with a tracing process that results in conclusions about the dengue fever suffered. While the waterfall method is used in the development of this expert system because the method can accommodate all stages of the system starting from the analysis of functional and non-functional system requirements, system design, coding, expert system testing and the last stage is expert system maintenance. The data used in this study used data from patients infected with mosquito bites at the Maos Health Center, Cilacap Regency in 2021. Testing is carried out using the black box testing method where the expert system is tested on end-users to determine the level of success and usability of the developed system. The questionnaire was given to 76 respondents with the results of the questionnaire: 91.9% indicating the level of user satisfaction, 89.6% indicating the level of effectiveness and 92.2% indicating the level of efficiency of the expert system. The output of this study is the conclusion of the disease suffered by the patient and the solution for handling it. The results of this study were used by the Puskesmas to determine the actions and therapies that were taken and carried out on the patient